2003
DOI: 10.1183/09031936.03.00113403
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of mast cell activation and leukotriene release after mannitol inhalation

Abstract: The aim of this study was to investigate if mannitol inhalation, as a model of exercise-induced bronchoconstriction (EIB), causes mast cell activation and release of mediators of bronchoconstriction.Urinary excretion of previously identified mediators of EIB was investigated in association with mannitol-induced bronchoconstriction. Twelve asthmatic and nine nonasthmatic subjects inhaled mannitol and urine was collected 60 min before and for 90 min after challenge. The urinary concentrations of leukotriene (LT)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
109
1
4

Year Published

2008
2008
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(119 citation statements)
references
References 34 publications
5
109
1
4
Order By: Relevance
“…The urinary LTE 4 concentration increased in asthmatic patients during the early asthmatic response after allergen challenge [21], in exercise-induced asthma patients during bronchoconstriction [22] and in aspirin-intolerant asthma after aspirin provocation [18]. However, none of the EP patients who participated in the present study, despite their asthma complications, experienced an asthmatic exacerbation or showed any symptoms of airway narrowing.…”
Section: Discussionmentioning
confidence: 53%
“…The urinary LTE 4 concentration increased in asthmatic patients during the early asthmatic response after allergen challenge [21], in exercise-induced asthma patients during bronchoconstriction [22] and in aspirin-intolerant asthma after aspirin provocation [18]. However, none of the EP patients who participated in the present study, despite their asthma complications, experienced an asthmatic exacerbation or showed any symptoms of airway narrowing.…”
Section: Discussionmentioning
confidence: 53%
“…There is strong evidence that the airway response to mannitol closely mimics central components of EIB, such as the activation of mast cells and eosinophils, resulting in the release of bronchoconstrictive mediators. 7,[9][10][11][12][13]19,20 However, the diff erences may lie in the intensity of the stimulus to the airways. Th e studies showing benefi t performed the exercise challenge until volitional exhaustion, which is a test that has a known low sensitivity to identifying EIB and which may induce milder airway responses in those with EIB.…”
Section: Discussionmentioning
confidence: 99%
“…Slower recovery from mannitol challenge does suggest a direct role of leukotrienes. 10,19 One study in humans has demonstrated worsening of daily peak fl ow and increased b 2 -agonist use with longer treatment of a daily dose of 3 g omega-3 fatty acids over 6 weeks in subjects with asthma and aspirin sensitivity. 24 Th e presumed mechanism for explaining the possible benefi cial eff ects of omega-3 fatty acids on infl ammatory pathways is through diversion of the production of bronchoconstricting prostaglandins and leukotrienes from the omega-6 substrate arachidonic acid to mediators biosynthesized from the alternative omega-3 substrates.…”
Section: Discussionmentioning
confidence: 99%
“…The detailed mechanisms are described in the literature. (29)(30)(31)(32)(33)(34) A DPI formulation of mannitol as a marketed pharmaceutical product (Bronchitol TM ) is approved in Europe and has been very recently approved in the United States. The polymorphic system of D-mannitol has been well documented.…”
Section: Introductionmentioning
confidence: 99%